Safety Comparison of Over the Counter Bleaching with Professionally Prescribed Home Bleaching Agent - Singh, Japsimretjit Kaur Manjit; Sengut, Masturah; Halim, Mohamad Syahrizal; Ab‑Ghani, Zuryati; Rahman, Normastura Abd (Medknow Publications, 2018)
Aims: This aimed to compare the colour changes, microhardness, and surface roughness of the human natural tooth after bleaching treatment with a professional home bleaching agent and over-the-counter (OTC) bleaching agent. Settings and Design: This was an in vitro study using extracted human teeth stained with human blood as specimens. Materials and Methods: Fifty-seven human natural teeth were embedded in acrylic of 2.5 mm thickness and 14 mm × 8 mm surface area. The samples were stained with human blood before they were divided into three groups (n = 19 per group) of control (C), Professional Bleaching Opalescence PF 15% (PB), and OTC Whitelight Tooth Whitening set (WL) before being treated with the respective bleaching agents for 10 days. Color changes were measured as colorimetric measurements (L*, a*, and b* values) were recorded during prestaining, poststaining, and postbleaching, while microhardness and surface roughness measurements were recorded for pre- and postbleaching. Statistical Analysis: Statistical analysis was done with SPSS (IBM Statistic, California, USA) version 22.0. Paired t-test and nonparametric analysis (Wilcoxon Signed-Rank Test) were used to analyze the data. P value was set as significant at P < 0.05. Results: The color changes in PB group was not significantly better compared with WL group (PB: 12.2 [4.07] and WL: 12.2 [4.32]). Whereas significant difference was noticed in microhardness after bleaching in PB group with a higher VHN number (500.4 [121.10]) compared with WL group (471.0 [114.47]) . The surface roughness (Ra) remain the same for all experimental groups. Conclusions: Both professional home bleaching agent and OTC bleaching agents showed similar efficacy, with no effect on surface roughness, and both caused an increase in microhardness.